3x(m-2)-2mx+9=5m+56 x=-2 m=?
Răspunsuri la întrebare
Răspuns de
5
Răspuns de
5
3 × ( - 2) ( m - 2 ) - 2 × ( - 2) m + 9 = 5 m + 56
- 6 m + 12 + 4 m + 9 = 5 m +56
- 2 m - 5 m = 56 - 21
- 7 m = 35 l : ( - 7 )
m = - 5
- 6 m + 12 + 4 m + 9 = 5 m +56
- 2 m - 5 m = 56 - 21
- 7 m = 35 l : ( - 7 )
m = - 5
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Istorie,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă